Sinergitas Guru dan Orang Tua dalam Pendampingan Belajar Anak Melalui Program Home Visit Wali di SMP Islam Jenu - Dewi Purwani; Amirur Rosidah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study analyses the synergy between teachers and parents through a home visit programme at Jenu Islamic Junior High School in supporting student learning assistance. A descriptive qualitative method was applied with data collection techniques through in-depth interviews, participatory observation, and documentation studies conducted over three months. The results show that the home visit programme, conducted regularly every three months, has succeeded in building effective collaboration between educators and parents in supporting student learning. Home visits not only strengthen the emotional bond between the school and families, but also enable teachers to understand the learning conditions of students directly in their home environment. This programme has had a significant impact on improving student motivation, attendance, and discipline. Despite facing obstacles such as scheduling difficulties and ethical challenges for female teachers in visiting the homes of male parents, the personalised approach applied in this programme proved to be capable of creating a more inclusive and sustainable educational environment. The home visit programme has become an effective mentoring model for improving the holistic academic and character development of students based on Islamic values.